Remote judging: the impact of video links on the image and the role of the judge. Issue 4 (23rd November 2018) - Rowden, Emma; Wallace, Anne
Abstract: Judges perform an important role on behalf of society, as impartial decision-makers, interpreting and applying the law, presiding over courtrooms and ensuring a fair trial. The image of the judge – how they are viewed culturally – reinforces their role, emphasising their authority and neutrality, thus supporting the legitimacy of the court as an institution. Increasingly, judges use video conferencing where either they, or other participants, are located away from the courtroom. Reporting on a three-year empirical study, this paper argues that the introduction of video-conferencing technologies in court has had a profound impact on the production, management and consumption of judicial images, with implications for the role of the judge. Video links challenge cultural assumptions about how the role of the judge is performed and what the image of the judge should be. We argue that greater congruence needs to be achieved over video links between that image and the role of the judge.